Study of the Influence of Specularity on the Efficiency of Solar Reflectors. (May 2015) - Alcañiz, C.; Martínez, N.; Heras, C.; Salinas, I.
Abstract: One of the critical aspects characterizing the behavior of the solar mirrors is their specularity[1], which characterizes its capability to focus all the reflected light into the solar collector. Specularity is highly dependent on the roughness of the substrate used to manufacture the mirror, so the roughness of the substrate is definitely a key point to develop products of the highest optical quality with potential to substitute the conventional floated-glass mirrors. A theoretical study taking into account the solar dispersion is developed to calculate the potential losses in parabolic through and power tower applications due to the use of non-completely specular mirrors. Then, a study of the relationship between the roughness of the different surfaces and its specularity has been developed to determine whether they have the potential to be used as substrates for new generation reflectors with an optimum efficiency or not. Besides, a study of the specularity of several commercially available mirrors is developed to determine its potential to be used in commercial solar plants. Finally, a 50 MW solar plant production case is developed for different reflector scenarios to estimate the production costs related to reflector losses in both solar concentrating technologies.